Desarrollo de una aplicación web que permita el monitoreo de incidentes a través de un gis, utilizando una aplicación a ser desarrollada para dispositivos móviles con sistema operativo android, que permita registrar la información georreferenciada. - Valencia Sánchez, Jhon Xavier (2018)
This document contains information about methodologies, tools, and procedures for to build quality software and meet customer's requirements, trying to meet all the needs of a software project with nice interface, a safe development and custom software for the client. The project has a many different ideas, but the principal is to register an incident and get the best information with a smartphone. The register captured with a smartphone has a many parts, for example the users need to get photography in this moment, information about this accident, get a exactly position and the level of the incidente. The information collected is processed in a type of plain text format called JSON, which allows obtaining records according to an adequate order that complies with this very light text format, the process ends with the registration of information is stored on a database not SQL. Firebase offers a database that supports the aforementioned format and adapting to certain rules that the end user requires. This register send to tool of Firebase, and the data save in database in the real time, the project content two parts, the first is to programming a website and the other is programming a mobile application, the website represent many registers capture in those moment and the administrator processes the record according to the level of the tragedy and the mobile application records the incidents. The development of these applications is intended to help the process of registering incidents that can be generated at any time, allowing the administrator of the website to take relevant actions to process these records, easily and very quickly.